Multimedia Interaktif Konsep Gravitasi Berorientasi Pada Literasi Sains - Hapsari Hapsari; Syarif Fitriyanto; Hermansyah Hermansyah; Fahmi Yahya; Sri Nurul Walidain (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
The objectives of this study were: 1) to determine the validity of interactive multimedia products oriented to science literacy in the concept of gravity and 2) to determine the response of prospective teachers to interactive multimedia products oriented to scientific literacy in the concept of gravity. This research is a type of research and development with the APPED model, but is limited to the evaluation stage. The research subjects were 2 validators and small-scale user trial subjects, namely 5 prospective physics teachers at Universitas Samawa in the second semester of the 2019/2020 academic year. The research and development results obtained were: 1) the product developed was categorized as very valid, with an average percentage of media validation reaching 87.3% and an average percentage of material validation reaching 82.4%; 2) the response of pre-service teachers to the products developed obtained an average percentage of 83.6% and was included in the very good category.